Parents' Knowledge of Preschool-Age Children About ADHD in Indonesia - Maulinda, Alida Shally; Lubis, Fitriani Yustikasari (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The emergence of attention-related problems is one of the indications of ADHD in preschool children. Early parental knowledge about ADHD can be a preventive aspect of the negative impacts that may arise. This study aimed to obtain qualitative data on Indonesian parents of preschoolers' general knowledge of ADHD, as well as their understanding of the symptoms of ADHD, and treatment/therapy for children with ADHD. The case study method used is the intrinsic case study. Six mothers of children between the ages of 3-5 participated in the study. Using open coding methods and NVivo software, the findings of semi-structured interviews were analyzed based on emerging themes. Several researchers were involved to complete the trustworthiness. The study's findings showed that there were still inaccurate perceptions and reluctance to look for information related to general knowledge, symptoms of ADHD, and treatment/therapy for children with ADHD. The findings show that a program is required to improve the knowledge of parents of children aged 3-5 about ADHD.Kemunculan gejala masalah atensi merupakan salah satu indikasi dari ADHD pada anak usia prasekolah. Pengetahuan orang tua sejak dini tentang ADHD dapat menjadi aspek preventif dari dampak negatif yang mungkin muncul. Tujuan dari penelitian ini adalah mendapatkan data kualitatif terkait pengetahuan orang tua dari anak usia prasekolah di Indonesia mengenai pengetahuan umum, gejala ADHD, serta pengobatan/terapi untuk anak dengan ADHD. Metode studi kasus yang digunakan adalah intrinsic case study. Penelitian dilakukan pada 6 orang ibu dari anak usia 3-5 tahun. Hasil semi-structured interview dianalisis berdasarkan tema yang muncul menggunakan perangkat lunak NVivo, dengan teknik open coding, serta melibatkan beberapa peneliti untuk melengkapi keabsahan data. Hasil penelitian menemukan masih terdapat persepsi yang kurang tepat dan keengganan untuk mencari informasi terkait pengetahuan umum, gejala ADHD, dan pengobatan/terapi untuk anak dengan ADHD. Implikasi dari hasil penelitian adalah diperlukan suatu program untuk meningkatkan pengetahuan orang tua dari anak usia 3-5 tahun mengenai ADHD.